(untitled) (Archives of Criminology, 2024)
Scholars have highlighted the crucial role that immigration officials play as “street-level bureaucrats” in the implementation of restrictive immigration policies. This study describes the working and decision-making practices of immigration officials in return procedures in Belgium, based on observations, expert interviews, and an analysis of case law. We demonstrate that their work primarily involves desk work and writing justifications in their decisions. Their decision-making is characterized by a heavy sense of pragmatism and standardization, primarily focusing on “what holds up in administrative court.” In return procedures, Belgian immigration officials therefore experience little need for legitimation work: from their perspective, legitimation primarily entails meeting administrative burdens of proof. Our analysis indicates that this distanced administrative system disadvantages the affected migrants, especially considering that the appellate body evaluates procedural aspects of the decision-making rather than conducting in-depth case (re-)evaluations.